2020
DOI: 10.1002/cssc.202001749
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids as Extractants for Nanoplastics

Abstract: Plastic waste in the ocean and on land in the form of nanoplastics is endangering food and drinking water supplies, raising the need for new strategies for the removal of plastic nanoparticles from complex media. In the present contribution we suggest considering ionic liquids as extractants, since they show several advantageous properties that may facilitate the design of efficient separation processes. Through varying the anion and the side chain at the cation, the interactions between the extractant and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Upon contact with NPs, the propensity of a model protein to form α-helical and β-loop secondary structures was shifted, with the changes being qualitatively different for PE and nylon 6,6 (Hollóczki and Gehrke 2019 ). Furthermore, the behavior of PE-NP in various solvents was explored through molecular modeling, revealing that in micro-structured amphiphilic liquids, e.g., ionic liquids, control over the disintegration (i.e., disentanglement) of NP analytes into free polymer chains can be achieved, which could be applied to extraction strategies for analytical purposes (Elfgen et al 2020 ).…”
Section: Ex Machina: Molecular Modeling To Understand the Adverse Eff...mentioning
confidence: 99%
“…Upon contact with NPs, the propensity of a model protein to form α-helical and β-loop secondary structures was shifted, with the changes being qualitatively different for PE and nylon 6,6 (Hollóczki and Gehrke 2019 ). Furthermore, the behavior of PE-NP in various solvents was explored through molecular modeling, revealing that in micro-structured amphiphilic liquids, e.g., ionic liquids, control over the disintegration (i.e., disentanglement) of NP analytes into free polymer chains can be achieved, which could be applied to extraction strategies for analytical purposes (Elfgen et al 2020 ).…”
Section: Ex Machina: Molecular Modeling To Understand the Adverse Eff...mentioning
confidence: 99%
“…22 In addition, molecular modeling has suggested that ILs can extract nanoplastics. 23 ILs have been combined with CPE, which increases the extraction ability of surfactants. This has been demonstrated for the extraction of five monoterpene glycosides from the Paeonia suffruticosa flower with a detection limit of 0.1 ng/mL.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Silver nanoparticles with recoveries of 75.7%–96.6% in consumer products were achieved with the use of ILs . In addition, molecular modeling has suggested that ILs can extract nanoplastics . ILs have been combined with CPE, which increases the extraction ability of surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several researchers have used ILs as extractants by adjusting the strength between the ILs and the nanoplastics. This has been achieved by changing the length of the alkyl side chain of the IL, and the nanoplastics could then be removed from aqueous solution [50]. From the above works, it can be seen that ILs are widely used within the fields of separation and extraction.…”
Section: Introductionmentioning
confidence: 99%